EVALUASI KETIDAKTEPATAN PEMBERIAN KODE REKAM MEDIS RAWAT JALAN DI RS PHC SURABAYA - Mahardika Nugraha; Dony Setiawan Hendyca Putra; Efri Tri Ardianto (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2021)
Codification is an activity to transform a diagnosis into a code consisting of letters and numbers.Inaccuracies of coding can slow the process of insurance claims and decrease the quality of medicalrecords. Preliminary study results showed a percentage of inaccuracy in the diagnostic code of 4documents of a total of 10 outpatient medical record documents at PHC Surabaya Hospital. This researchaims to evaluate the correctness of an outpatient medical record file in Surabaya's PHC Hospital. This typeof research used qualitative research. The samples were 44 documents of the outpatient medical record inJanuary 2020. Data collection techniques using observation and documentation. The results of the studyshow that the code inaccuracies in an outpatient medical record document of 13 (29.5%) improper codeand 21 (70.5%) of the right code. The cause of its absence was an error in the code-granting suspect of15.4%, a mistake in giving control code and therapy of 61.5%, and an error in giving the fourth character inthe case of diabetes mellitus by 23.1%. Factors that lead to inaccuracy in the coding of an outpatientmedical record were the less thorough officers in conducting medical record reviews as well as mistakes indetermining the old case and new cases. The suggestions provided by researchers are to conduct routinecoding audits, repair SOP, socialization about the correct encoding procedures, and make a note for thecode which is often to be used.